(untitled) (Revista do Centro de Estudos Portugueses, 2007)
Resenha: BENJAMIN, Walter. Passagens de Walter Benjamin. TIEDEMANN, Rolf; BOLLE, Willi; MATOS, Olgária Chaim Feres (Org.). Trad. Irene Aron e Cleonice P. B. Mourão. Belo Horizonte: UFMG/Imprensa Oficial de São Paulo, 2006.